2020
DOI: 10.1155/2020/3867401
|View full text |Cite
|
Sign up to set email alerts
|

Research on Two-Level Price-Fluctuation Supply Chain Ordering Strategy Problem

Abstract: Uncertainties from retail price-fluctuation sales as well as constraints from suppliers make it difficult for retailers to place accurate orders, which have a great impact on the whole supply chain. Thus, this paper studies a supply chain ordering problem for two-level price-fluctuation sales and establishes a bilevel programming model by Copula function measuring the correlation between price and demand. The optimal order quantity is derived by transforming the bilevel programming model into a single-level mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In China, Huang (2020) indicated that in the initial months of lockdown, February and March, the PFSC was severely hit in all stages, even the export of products, revealing a more CEP denotes the circular economy practices, including digital technology, reduction in waste, water and electricity (Khan and Zhang, 2020;Nandi et al, 2020;MacArthur, 2020;Giudice et al, 2020;Avraamidou et al, 2020;Kaipia et al, 2013;Corrêa and Corrêa, 2020) Demand and price (DP) DP explains the demand and supply mismatch and fluctuation in product prices during pandemic (Zheng et al, 2020;Ali and Khan, 2020;Rajput et al, 2020;Kumar et al, 2020a, b;Sharma et al, 2020;Tr€ oster and K€ ublb€ ock, 2020) PFSC resilience (PFSC)…”
Section: Pfsc and Covid-19mentioning
confidence: 99%
“…In China, Huang (2020) indicated that in the initial months of lockdown, February and March, the PFSC was severely hit in all stages, even the export of products, revealing a more CEP denotes the circular economy practices, including digital technology, reduction in waste, water and electricity (Khan and Zhang, 2020;Nandi et al, 2020;MacArthur, 2020;Giudice et al, 2020;Avraamidou et al, 2020;Kaipia et al, 2013;Corrêa and Corrêa, 2020) Demand and price (DP) DP explains the demand and supply mismatch and fluctuation in product prices during pandemic (Zheng et al, 2020;Ali and Khan, 2020;Rajput et al, 2020;Kumar et al, 2020a, b;Sharma et al, 2020;Tr€ oster and K€ ublb€ ock, 2020) PFSC resilience (PFSC)…”
Section: Pfsc and Covid-19mentioning
confidence: 99%
“…This study discusses the control of multi-item inventory for packaging made from paper rolls which consider fluctuations in demand and prices of goods. Zheng et al (2020) studies a supply chain ordering problem for two level price-fluctuation sales and establishes a bilevel programming model by Copula function measuring the correlation between price and demand.…”
Section: Literature Reviewmentioning
confidence: 99%